2017
DOI: 10.1007/978-3-319-67008-9_17
|View full text |Cite
|
Sign up to set email alerts
|

Europeana: What Users Search for and Why

Abstract: Abstract. People use digital cultural heritage sites in different ways and for various purposes. In this paper we explore what information people search for and why when using Europeana, one of the world's largest aggregators of cultural heritage. We gathered a probability sample of 240 search requests from users via an online survey and used qualitative content analysis complemented with Shatford-Panofsky's mode/facet analysis for analysing requests to visual archives to investigate the following: (i) the bro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…The task aims to process the textual information from the various sources of the systems. To this end, the module integrates proper packages, i.e., Youtube-dl 5 , for accessing and extracting video metadata and OpenCV 6 for extracting visual features from frames. In detail, the following elements are extracted and grouped: (i) The video info: the textual description of each video and its title are extracted and aggregated after removing noisy elements (e.g., links or emojis).…”
Section: Metadata Extractionmentioning
confidence: 99%
“…The task aims to process the textual information from the various sources of the systems. To this end, the module integrates proper packages, i.e., Youtube-dl 5 , for accessing and extracting video metadata and OpenCV 6 for extracting visual features from frames. In detail, the following elements are extracted and grouped: (i) The video info: the textual description of each video and its title are extracted and aggregated after removing noisy elements (e.g., links or emojis).…”
Section: Metadata Extractionmentioning
confidence: 99%
“…For instance, according to a study on the Tate's website, 70% of users are non-art specialists (Villaespesa and Stack, 2015), and, similarly, this group represents 76% of the users of the Museums National Liverpool's website (Walsh et al, 2020). Moreover, there are users that are looking for inspiration or browse without a specific goal, and browsing by subject provides an entry point to the collection (Clough et al, 2017;Skov and Ingwersen, 2008;Villaespesa, 2019). Findings from the data point out the need to provide experiences that encourage exploration and serendipity based on other concepts and vocabularies.…”
Section: Human and Machinegenerated Tagsmentioning
confidence: 99%
“…Darby and Clough found that these users return to their search and preferred resources frequently, that the search is ongoing and open-ended, and resources such as newspaper collections are used more in a later stage of the research. Another study used pop-up surveys to investigate the motives for search within a cultural heritage site (Clough et al, 2017).…”
Section: Related Workmentioning
confidence: 99%